Thực trạng tham gia của các lực lượng trong hoạt động giáo dục thẩm mĩ theo tiếp cận Reggio Emilia cho trẻ mẫu giáo: nghiên cứu tại Hà Nội, Đà Nẵng và Thành phố Hồ Chí Minh - Dương, Thị Hoàng Yến; Nguyễn, Thị Thành; Nghiêm, Thị Đương (Tạp chí Giáo dục, 2025)
Attracting forces inside and outside the school to participate in aesthetic education activities according to the Reggio Emilia approach for preschool children at preschools plays a very important role in ensuring the effectiveness of this activity. The survey results of 738 managers and teachers at preschools in Hanoi, Da Nang and Ho Chi Minh City show that mobilizing forces including pedagogical experts/consultants, managers, preschool teachers, parents and the community to participate in aesthetic education activities according to the Reggio Emilia approach still has both advantages and difficulties, especially in the group of parents and the community. On that basis, the study proposes recommendations to improve the effectiveness of managing aesthetic education activities according to the Reggio Emilia approach at preschools. The participation of forces inside and outside the school according to the Reggio Emilia approach needs to be promoted flexibly, in accordance with the specific conditions of each educational institution and local reality, in order to expand the learning environment, promote creativity and maximize the aesthetic potential of children.